Household and Environmental Risk Factors for Kala-azar: A Case-Control Study in Tertiary Care Hospital of Bangladesh (Journal of Science Foundation, 2017)
Background: Visceral Leishmaniasis (VL), commonly known as Kala-azar is a chronic febrile disease occurs widely throughout the world. There are many risk factors which can influence the causation of kala azar in Bangladeshi people.Objective: The aim of the present study is to describe the Sociodemographic, household and environmental risk factors of kala-azar among a case series of Bangladeshi patients. Method: This case control study was carried out at inpatient department of Community Based Medical College Hospital, Mymensingh from July 2010 to June 2011, for a period of 1(one) year.  The study samples were clinically and parasitologically confirmed kala-azar cases. The controls were rK 39 strip test negative hospitalized cases admitted for other reason.Results: Univariate analysis showed that nature of wall in the main structure, floor of the house, presence of cracks and crevices in walls, presence of a granary inside houses and presence of bamboo trees near houses, were risk factors for kala-azar. Multivariate analysis showed that Presence of cracks and crevices in walls (OR=3.429, 95%CI=1.037-11.338, P =0.043) and presence of bamboo tree around houses (OR=5.652, 95%CI =1.368-23.347, P =0.017) in rural areas of study region, were significant risk factors for kala-azar.Conclusion: These findings have important practical implications because they suggest that on improving housing and environmental conditions  in rural areas, may be particularly effective in reducing the incidence of kala-azar and its transmission of infection by sand fly vectors.Journal of Science Foundation, 2016;14(2):56-61